Um procedimento para identificação de oportunidades e definição de conceito de produtos em uma pequena empresa de tecnologia em internet móvel - Bruno Augusto Pfeilsticker (2002)
The Internet is nowadays one of the most important ways of exchanging data in the world. Its importance for the world-wide commerce is increasing, as agent of e-commerce. The mobile Internet makes possible that users exchange data remotely, although not offering yet the proper conditions of usability and efficiency, it is expected to be a world-wide trend. As being a very new market, it doesnt present a defined business model. It presents a very fast development cycle of products and the majority of its products ideas are originated abroad. Therefore it becomes necessary that the mobile internet companies develop a new process optimizing their products development, reaching better new product idea selection and allowing a better product concept definition. It is considered in this work that the theories of development of traditional products, normally origineted in the major corporations, could be applied in the related mobile internet company, considering some changes in its content and depth. It is intended in this work to consider a procedure of management of the Oportunity Identification and concept definition of products activities, built through interventions in a small company of technology in mobile Internet. The worked points of improvement had been: 1- Necessity of systematization and communication of the identified chances and its markets; 2- Necessity of a comparative evaluation system between the variuos opportunities, in order to indicate which would be the best ones for the company; 3- Necessity of a formal functionalities captation mechanism